PRINCIPLES OF TEXT-MAKING OF A POLITICAL PROGRAM AS A SPEECH GENRE OF POLITICAL DISCOURSE - Н. В. Кондратенко (Записки з українського мовознавства, 2017)
The article is devoted to the analysis of the political program as one of the language genres of Ukrainian political discourse. The purpose of the paper is to study the specifics of a political program as a speech genre at creating and maintaining a political image. The goal has determined the solution of the following tasks: to characterize the political program as speech genre; to discover the structural and compositional features of political programs; determine the verbal specificity of political programs; analyze the implementation of the image function in political programs. The object of research is Ukrainian political discourse in the linguistic and pragmatic aspect, and the subject is the speech genre of the political program. The material was the texts of official and promotional political programs of well-known Ukrainian politicians and political parties (2004-2016). The concept of the speech genre is outlined, classifications of speech genres of political communication are presented, author’s approach to definition of types of political speech genres is proposed. The performative nature of the political program is proved and the features of informative and image speech genres are singled out in it. The basic principles of constructing the text of political programs are presented. The political program has signs of two types of speech genres of political discourse – informative and imaginative, but due to the dominance of the facts in software texts, we assign them to the image. They are aimed at presenting ideological landmarks and proposals of a political subject, based on political performances and subject to the three text-based principles – the thesaurus, the constrastic and the dialogic. Prospects for the study are the further development of the typology of speech genres of political discourse.